Developments in surgical treatment of pleural empiema - Kondov B; Cholanceski R; Kondov G; Jovanovski Srceva М; Cvetanovska M; Ferati I (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University in Skopje, R.N.Macedonia, 2023)
Thoracic empyema is the accumulation of pus within the pleural cavity. The most frequent cause is direct contiguous spread of infection, the most frequent from lung infection. Current management of empyema is based on local empirical practice as there is no consensus on an optimal regimen. It is estimated that 40% (7-57%) of pneumonia, results with parapneumonic effusion, out of which 10% develop empyema of pleural space. Treatment covers antibiotics, pleural drainage, pleural drainage and use of fibrinolytics, VATS early debridement, VATS decortication, open decortication, open pleural window and thoracoplasty. The choice of adequate treatment is according to stage of empyema: I (exudative stage) - thoracic drainage, II (fibrinopurulent stage) - thoracic drainage with fibrinolytics and VATS debridement or VATS early decortication and for III (empyema in organization stage) - VATS or open decortication or later thoracoplasty. Early VATS debridement effectively manages simple parapneumonic effusions. VATS decortication has efficacy for managing early-stage empyema. In the past (2011-15) period 234 patients with empyema were treated, out of which 124 (52.99%) of empyema were treated with pleural drainage, 105 (44.87%) were treated with open decortication and 5 (2.14%) with thoracoplasty. In the last 6 months of 2023, 21 patients were treated, 19 (90.5%) male and 2 (9.5%) female. Unfortunately, in the last 6 months only 5 (23.8%) of the patients were treated only with pleural drainage, 4 (19%) patients were treated with VATS debridement or early decortication and 12 (57.14%) patients were treated with pleural drainage that finished with open decortication. This situation suggests that, unfortunately, empyema was detected in advanced stage that needed aggressive surgical treatment. Early detection of parapneumonic effusion and treatment in this stage will prevent development of empyema and need of aggressive treatment.
Keywords: pleural empyema; thoracic drainage; VATS decortication